Effect of Operating Parameters on Ethanol–Water Vacuum Separation in an Ethanol Dehydration Apparatus and Process Modeling with ANN - S., Karimi; B., Ghobadian; G., Najafi; A., Nikian; R., Mamat (De Gruyter, 2014)
Bioethanol has been found to be a suitable substitute for gasoline in internal combustion engines. It could be used either in an undiluted form or blended with gasoline. To blend the ethanol and gasoline, the water content of ethanol should reach 0.5% or less. In the present research work, 3A Zeolite was used as an absorbent with vacuum distillation. The effects of the operating parameters such as temperature, vacuum pressure and vapor flow rate on ethanol–water separation were investigated. Final ethanol concentration was obtained at the end of every run as well as the concentration of outlet ethanol. Both linear regression and ANN design were used to determine the best fit for two final parameters. The optimum condition was obtained at 0.4 bar vacuum pressure and 20 l/min ethanol–water vapor flow rate. ANN model is more qualified to the simulation of outspread data while the linear regression is not. L10L10 mode and L5T10 mode provide the best results for final concentration and total time, respectively. The Trainlm Algorithm like the previous research training algorithm is the best.